2004
DOI: 10.1152/ajpgi.00189.2003
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid induces interleukin-8 production by Crohn's human intestinal smooth muscle cells via arachidonic acid metabolites

Abstract: Previously we reported that linoleic acid (LA), but not oleic acid, caused a marked increase in the secretion of IL-8 by Crohn's human intestinal smooth muscle (HISM) cells. Antioxidants inhibited this response, implicating a role for oxidative stress and NF-κB, a transcription factor for IL-8 that is activated by oxidative stress. In this study, we examined two mechanisms whereby LA, the dietary precursor for arachidonic acid (AA), could increase the production of IL-8 via activation of AA pathways: 1) by gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…To determine whether AA metabolites are involved in Ang II-induced RGS2 mRNA up-regulation in VSMC, cells were incubated with the lipoxygenase inhibitor nordihydroguaiaretic acid, the cyclooxygenase inhibitor indomethacin, or the cytochrome P450-dependent epoxygenases inhibitor 17-octadecynoic acid, respectively, prior to Ang II or AA stimulation. Interestingly, we found that nordihydroguaiaretic acid (30 M) (60, 61) completely and indomethacin (50 M) (61,62) partially, but significantly, inhibited Ang II or AA-stimulated RGS2 mRNA up-regulation, whereas 17-octadecynoic acid (10 M) (63) had no inhibitory effect (Fig. 8E).…”
Section: Vsmc Involves Enzymatic Activation and Accumulation Of Its Rmentioning
confidence: 91%
“…To determine whether AA metabolites are involved in Ang II-induced RGS2 mRNA up-regulation in VSMC, cells were incubated with the lipoxygenase inhibitor nordihydroguaiaretic acid, the cyclooxygenase inhibitor indomethacin, or the cytochrome P450-dependent epoxygenases inhibitor 17-octadecynoic acid, respectively, prior to Ang II or AA stimulation. Interestingly, we found that nordihydroguaiaretic acid (30 M) (60, 61) completely and indomethacin (50 M) (61,62) partially, but significantly, inhibited Ang II or AA-stimulated RGS2 mRNA up-regulation, whereas 17-octadecynoic acid (10 M) (63) had no inhibitory effect (Fig. 8E).…”
Section: Vsmc Involves Enzymatic Activation and Accumulation Of Its Rmentioning
confidence: 91%
“…IL-8 production in intestinal epithelial cells increases in response to pro-inflammatory cytokines such as tumor necrosis factor-a [37,38] and IL-1 [32], or oxidative stress such as that by H 2 O 2 [32,39,40]. To determine whether We next treated Caco-2 cells with hemin at various concentrations for 24 h, and the culture medium was collected for IL-8 determination by ELISA.…”
Section: Effect Of Hemin On Il-8 Mrna Expression and Il-8 Production mentioning
confidence: 99%
“…6,12 Among the various unsaturated fatty acids, many studies have shown that -3 polyunsaturated fatty acids have a better effect than that of -6 polyunsaturated fatty acids. 7,8,[13][14][15][16] However, the effects of specific forms of dietary fat on IBD remain controversial. 2,3 Attention has recently been paid to adiponectin, a substance released from adipocytes, because of its involvement in the pathophysiology of many lifestyle-related diseases such as diabetes mellitus, 17 atherosclerosis, 17 and nonalcoholic steatohepatitis.…”
mentioning
confidence: 99%